Green patenting and voluntary innovation disclosure - Skinner, A. Nicole; Valentine, Kristen (Review of Accounting Studies, 2026)
We investigate whether green innovators voluntarily provide innovation disclosure to reduce processing costs for stakeholders and gain green-specific disclosure benefits. We observe that green patenting firms provide more innovation disclosure in conference calls than do other innovating peers, controlling for patent value. Using a patent-call unit of analysis, we also provide within-firm evidence that managers highlight their green inventions more on conference calls relative to their other inventions. Green innovators provide more innovation disclosure when the costs of processing patent information are higher and anticipated disclosure benefits are greater. We find some evidence that innovation disclosure is positively associated with green fund ownership and stronger market responses to conference calls as well as proxies for ESG-related reputation. Our findings highlight both capital market and social capital benefits as motivating forces for voluntary innovation disclosure and suggest the nature of a firm’s innovations can impact its information environment.